PENINGKATAN KEMAMPUAN LITERASI SISWA MELALUI POSTER SESSION PADA MATERI KALIMAT PERINTAH DI KELAS V UPT SDN 065012 MEDAN TUNTUNGAN TAHUN AJARAN 2024/2025 - Dian Natalia Pasaribu; Asnita Hasibuan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aimed to improve the literacy skills of fifth-grade students at UPT SDN 065012 Medan Tuntungan in learning imperative sentences through the implementation of the poster session strategy. The research employed a Classroom Action Research (CAR) method conducted over two cycles, each comprising the stages of planning, implementation, observation, and reflection. The participants of the study consisted of 17 students. Data were collected through written tests and observations of student activities and analyzed using descriptive quantitative methods. The results of the study indicated an improvement in students’ literacy skills following the application of the poster session strategy. In Cycle I, the average student score was 60.58, with a classical mastery level of 41.17%. After revisions made in Cycle II, the average score increased to 78.23 and the classical mastery level reached 82.35%. Moreover, observations of students’ literacy skills demonstrated an improvement. In the aspect of writing imperative sentences, the percentage increased from 66.66% to 86.27%, while in the aspect of communicating imperative sentences, the percentage rose from 63.23% to 81.86%. The application of the poster session strategy proved effective in enhancing students’ literacy skills by promoting active engagement, creativity, as well as visual and verbal communication abilities. This strategy enabled students to compose imperative sentences contextually through engaging visual media. Thus, the poster session can serve as an innovative alternative instructional method for strengthening Indonesian language skills at the elementary school level.